1973
DOI: 10.1289/ehp.7305149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,3,7,8-tetrachlorodibenzo-p-dioxin on the immune system of laboratory animals.

Abstract: Images FIGURE 1. FIGURE 2. FIGURE 3. a FIGURE 3. b FIGURE 4. FIGURE 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(33 citation statements)
references
References 20 publications
4
29
0
Order By: Relevance
“…Different TCDD doses are probably a cause of a distinct white blood cell picture in rats with experimentally induced pleuritis being under the effect of TCDD received in current and recent studies. According to Vos et al [54, 55], low TCDD doses (about 0.2 μg per 1 kg of body weight) influence the humoral response displaying itself through the increase of α- and β-globulin levels and reduction of the ability for antibody synthesis in mice plasma. The dioxin’s affinity to DNA molecules suggests that dioxins could be responsible for the immunity decrease [45, 54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…Different TCDD doses are probably a cause of a distinct white blood cell picture in rats with experimentally induced pleuritis being under the effect of TCDD received in current and recent studies. According to Vos et al [54, 55], low TCDD doses (about 0.2 μg per 1 kg of body weight) influence the humoral response displaying itself through the increase of α- and β-globulin levels and reduction of the ability for antibody synthesis in mice plasma. The dioxin’s affinity to DNA molecules suggests that dioxins could be responsible for the immunity decrease [45, 54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…TCDD is known to induce a pronounced atrophy of thymus, spleen, and to a lesser extent, peripheral lymph nodes of rats, mice, and guinea pigs (8,19,20). Although there is species variation in the degree and severity of other organ effects, the effects of TCDD on lymphoid containing tissues is consistent in all species.…”
Section: Effects Of Tcdd On Immunitymentioning
confidence: 97%
“…Studies of immune function in several species of animals exposed as adults found cellular immune capabilities to be impaired (8,9). This circumstance combined with the teratogenic data that demonstrate the ability of TCDD to gain access to the fetus prompted investigation of the possible effect(s) of TCDD on the developing immune system.…”
Section: Effects Of Tcdd On Immunitymentioning
confidence: 99%
“…*O* Moreover, TCDD in concentrations up to 0.1 pM has been found to have no cytotoxic effect on 23 cell lines cultured from tissue sensitive to TCDD in vivo, including lymphoc y t e~.~~~ In TCDD-exposed rats and mice, no overt thymocyte destruction is evident either: some investigators have reported the lack of cell death,303,432 whereas other studies have revealed low numbers of pyknotic thymocytes in moribund animals. 195,433 After administration of a high dose of TCDD, severe cortex atrophy was also seen in moribund guinea pigs together with considerable destruction of thymocytes, the debris being engulfed by tingible body M$.243, 433 Recently, the role of Fas (CD 95), an important molecule involved in the induction of apoptosis, was investigated in mice bearing homozygous lpr mutation, which fail to express Fas314 When TCDD was administered orally at dose levels of 0.1 to 5 pgkgld, it was found to be less toxic to the thymocytes from C57BL/6 lpr/lpr mice (Ahresponsive, Fas-), when compared with wild-type C57BL/6+'+ mice (Ah-responsive, Fas+). The Fasmice needed tenfold more TCDD to induce similar toxicity in the thymus as the Fas+ mice.…”
Section: A Thymocyte Apoptosismentioning
confidence: 99%